Experimental investigation on the permeability function of unsaturated soil with multi-modal porosity - Zhafri Bin Zainal Ariffin Abbas (Nanyang Technological University, 2022)
Unsaturated soils are located above the groundwater table (G.W.T) and unsaturated soil slopes are more susceptible to rainfall-induced slope failures. As such, infiltration of water would cause an increase in water content, subsequently decreasing the matric suction of soil, thus reducing shear strength and the stability of the slope. Therefore, the hydraulic properties, mainly the soil water characteristic curve (SWCC) and permeability function of unsaturated soil play a fundamental role in rainfall-induced slope failures. Adding various materials such as activated carbon onto sand and kaolin enhances the illustration of a multi-modal SWCC, which exhibits greater water retaining capabilities, improving plant growth on slopes; one method to mitigate slope failure as it provides erosion protection and reinforcement to the soil. The objective of this study is to conduct experimental investigations on the permeability function of unsaturated soils with multi–modal porosity and comparing the two types of methods used in the experiments. SKP which comprised sand, kaolin, and powdered activated carbon, and SKG which comprised sand, kaolin, and granular activated carbon were used for this experiment. The tests and experiments involved the use of dynamic and standard compactions, followed by index property tests, shrinkage tests. SWCC and permeability tests were conducted using two different types of methods. The first method involved the use of axis translation technique (Hilf, 1956), the conventional drying method involved the use of Tempe Cell and pressure plate to obtain the SWCC and subsequently, the estimated permeability function of the soil. The second method involved the use of Schindler’s evaporation method which used the HYPROP and osmotic tensiometer permeameter setups that directly measured SWCC and permeability function. The experimental results confirm that both SKP and SKG exhibit a trimodal SWCC, and three significant drops in permeability, under unsaturated condition. Thus, the three sets of parameters ( a, m and θ_s) were used to best fit the trimodal SWCC curve using an extension of Satyanaga’s et al., (2013) equation. Analyses using the hydraulic properties obtained from the tests and the finite element seepage software, SEEP/W, the concept that soil specimens with a higher percentage in fines produced a lower permeability than the coarse grain soil specimens are demonstrated. The test also showed that Schindler’s evaporation method gave a slightly greater matric suction and the permeability function for the same water content than the conventional drying method. Despite the slight difference, both methods exhibited trimodal SWCC and permeability functions that are almost identical.